Acute Atrial Tachyarrhythmias During Epidural Analgesia for Cesarean Section in a Gestational Diabetic Woman. Issue 3 (July 1986) - Amar, David; Schuss, Marvin; Marx, Gertie F.
Abstract : We observed the development of acute atrial tachyarrhythmias in a euthyroid parturient with gestational diabetes but no history of cardiac disease who was undergoing emergency cesarean section under epidural analgesia. The arrhythmias appeared to have been precipitated by acute hypokalemia secondary to diet-induced hyperglycemia at the time of peak cardiac stress.